Pendampingan Pengembangan Produk Dan Strategi Pemasaran Kopi Manggis Sebagai Produk Unggulan UMKM Lombok - Putri Reno Kemala sari; I Nengah Arsana; Rusdi; Rosyia Wardani; Syaiful Amri; Elvina Setiawati (Valid Jurnal Pengabdian, 2026)
This community service activity aims to enhance the competitiveness of Lombok's SMEs thru intensive business consultations in developing innovative product marketing strategies. The service partner is an MSME actor who develops mangosteen coffee products as a combination of two regional flagship commodities. The methods used include intensive business consultations, assistance in developing marketing strategies, and strengthening branding. The results of the activities show that the partners successfully understood the product positioning in the market, were able to design marketing strategies that align with the target consumers, and had a clear business roadmap for business development. The mangosteen coffee product produced has a unique quality as an innovative product based on local wisdom with promising market potential.